Prognostic Modelling for Smart cities using Smart Agents and IoT: A Proposed Solution for Sustainable Development - Ul Ahsaan, Shafqat; Kumar Mourya, Ashish (EAI Endorsed Transactions on Smart Cities, 2021)
Currently, Scientists are working on smart cities for providing artificial intelligence based smart facilities and services that can tackle different problems raised by rapid urbanization and boom in population growth. The Internet of things is also being used with other smart technologies to provide better solutions to the environment. It is also known as a network of networks. Mobile agent technology has also gained more attention. We are using it with different internet-based services. In this research, we have proposed two models with a sustainable approach. Our first model focused on monitoring air quality which consisted of several sensors, Arduino Uno board, and Raspberry Pi 3. The Second model explores the potential of the mobile agent technique to lever the Internet of Things in the modernization and personalized services for Smart Cities.
Keywords: Smart City; Internet of Things (IoT); Software Agent; Mobile Agent; Artificial Intelligence (AI); Digital Initiative; Arduino Uno board; Raspberry Pi 3